Reactive oxygen species-responsive RNA interference - Rühle, Jennifer; Klemt, Insa; Abakumova, Tatiana; Sergeeva, Olga; Vetosheva, Polina; Zatsepin, Timofei; Mokhir, Andriy (Chemical Communications, 2022)
Due to oxidative instability, arylboronic acids are not compatible with the solid-phase synthesis of nucleic acids. We solved this problem and, based on these findings, developed siRNA prodrugs activated in the presence of reactive oxygen species (ROS) in vivo. These prodrugs can be used for specific targeting of ROS-rich cancer cells.
CRIS-Team WoS Importer:2022-04-01